Embedded liberalism or embedded nationalism? How welfare states affect anti-globalisation nationalism in party platforms. Issue 1 (2nd January 2022) - Burgoon, Brian; Schakel, Wouter
Abstract: In industrialised democracies, welfare state provisions have offsetting implications for anti-globalisation nationalism, central to the position taking of populist radical-right parties. On the one hand, social protection has an 'embedded liberalism' effect, mitigating economic insecurities associated with globalisation and thereby dampening anti-globalisation nationalism. On the other hand, social protection has an 'embedded nationalism' effect, awakening worries that globalisation may undermine hard-won provisions, thereby deepening anti-globalisation. This paper argues and finds evidence that which of these dynamics predominates depends on the particular kind of anti-globalisation debated and on the particular party family doing the debating. Welfare effort does generally dampen anti-globalisation nationalism, but it can deepen more than dampen anti-globalisation with respect to immigration and EU-integration that more directly impact existing national welfare provisions. Welfare effort can also deepen more than dampen anti-globalisation among radical-right and radical-left parties taking issue-ownership of anti-globalisation and of protecting national welfare-state competencies from global pressure.